Sentimen Analisis Rumah Makan Rawon Sakinah Dengan Metode Naïve Bayes Classifier - M.Ridwan Ridwan; Rudi Hariyanto; Muslim Alamsyah (CV. Akira Java Bulu, 2024)
Abstract-Rawon Sakinah Restaurant is a famous restaurant in the city of Pasuruan. If you are looking for typical culinary delights from Pasuruan City, local residents will unanimously answer Rawon Sakinah. This restaurant has been around for 30 years. located at Jalan Bangilan No. 80 Pasuruan City. In this study, the sentiment of visitors to the Rawon Sakinah Restaurant will be analyzed based on Google reviews. To find out the reviews of visitors to the Rawon Sakinah Restaurant whether the sentiment reviews are positive or negative. The stages of data analysis are text processing to clean data, weighting words, labeling data into positive and negative classes, classifying, and visualizing data with wordcloud. positive sentiments amounted to 237 and negative sentiments amounted to 13. In this study using the Naïve Bayes method. The accuracy value obtained for the Naïve Bayes method is 92% with a positive sentiment. From the results of the review sentiment research, it was found that the majority of visitors had positive sentiments.